A Comparative Study on Differences of Students’ Academic Achievement between More and Less Parental Involvement in Bangkok Christian International School - Ye, Yan; Jiang, Fuxiu (Scholar: Human Sciences, 2014)
This study mainly aimed to compare the primary school students’ academic achievements between more and less parental involvement in Bangkok Christian International School (BCIS), Thailand. The instrument of this study was a questionnaire, including questions to survey the student parents’ demographics, the levels of parental involvement and to obtain the students’ academic achievements. The questionnaires were distributed to all 60 students’ parents in Grade 5-6 in Bangkok Christian International School (BCIS), Thailand, 57questionnaires were returned and validly completed. The study used frequency and percentage to report the student parents’ demographics firstly; used means and standard deviations to identify the levels of parental involvement in BCIS, lastly used a t-test (one way) to determine the difference of students’ achievement between more and less parental involvement. A significant difference of students’ achievement between more parental involvement and less parental involvement was found by the end of the study. Therefore, discussion and recommendations on how to provide more parental involvement for the students were provided in the last part of the study.